Characterization of relaxin 3 and its receptors in chicken: Evidence for relaxin 3 acting as a novel pituitary hormone - Lv, Can; Zheng, Huilu; Jiang, Biying; Ren, Qin; Zhang, Jiannan; Zhang, Xin; Li, Juan; Wang, Yajun (Frontiers in Physiology, 2022)
Mammalian relaxin (RLN) family peptides binding their receptors (RXFPs) play a variety of roles in many physiological processes, such as reproduction, stress, appetite regulation, and energy balance. In birds, although two relaxin family peptides (RLN3 and INSL5) and four receptors (RXFP1, RXFP2, RXFP2-like and RXFP3) were predicated, their sequence features, signal properties, tissue distribution and physiological functions remain largely unknown. In this study, using chicken as experimental model, we cloned the cDNA full length of cRLN3 gene and two receptors (cRXFP1 and cRXFP3) genes. Using cell-based luciferase reporter assays, we demonstrate that cRLN3 is able to activate both cRXFP1 and cRXFP3 for downstream signaling. The cRXFP1, rather than cRXFP3, is a cognate receptor for cRLN3, which is different from the mammals. Tissue distribution analyses reveal that cRLN3 is highly expressed in the pituitary with lower abundance in hypothalamus and ovary of female chicken, together with the detection that cRLN3 co-localizes with pituitary hormone genes LHB/FSHB/GRP/CART and its expression is tightly regulated by hypothalamic factors (GnRH and CRH) and sex steroid hormone (E2), present study supports that cRLN3 may function as a novel pituitary hormone involving female reproduction.